2021
DOI: 10.3390/coatings11020138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In Situ Graphitic Nanocarbon Coatings on Cycling Performance of Silicon-Flake-Based Anode of Lithium Ion Battery

Abstract: We coated graphitic nanocarbons by thermal chemical vapor deposition (CVD) on silicon flakes recycled from the waste of silicon wafer manufacturing processes as an active material for the anode of lithium ion battery (LIB). Ferrocene contains both iron catalyst and carbon, while camphor serves as an additional carbon source. Water vapor promotes catalytic growth of nanocarbons, including carbon nanotubes (CNTs), carbon fibers (CFs), and carbon films made of graphitic carbon nanoparticles, at temperatures rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…According to Eqs. ( 4)- (5), assuming that the radiation heat transfer between the power battery and the external environment is zero, the convection heat transfer coefficient with the external environment is 5W m −2 •K −1 , a = 0.01593, b = 28.41552, the average heat production rate of the square iron-shell lithium iron phosphate power battery at the 4C discharge rate is 27.81 W.…”
Section: Theory Of Battery Heat Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Eqs. ( 4)- (5), assuming that the radiation heat transfer between the power battery and the external environment is zero, the convection heat transfer coefficient with the external environment is 5W m −2 •K −1 , a = 0.01593, b = 28.41552, the average heat production rate of the square iron-shell lithium iron phosphate power battery at the 4C discharge rate is 27.81 W.…”
Section: Theory Of Battery Heat Productionmentioning
confidence: 99%
“…The power battery module is the core component of the energy supply, and its safety assessment, management, and protection have received extensive attention in recent years 4 . Among various rechargeable batteries such as lead-acid, sodium-sulfur, and lithium-ion batteries, lithium-ion batteries have many merits, such as elevated energy density, substantial specific capacity, minimal environmental impact, stable functionality, and prolonged cycle life 5 . Therefore, it is also considered the most suitable power source for new energy vehicles 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Novikov et al 28 used ferrocene as an effective catalyst to convert CO 2 into CNTs and revealed the nucleation mechanism of CNTs. Tzeng et al 29 synthesized silicon/carbon nanotubes/carbon fibers (Si/ CNTs/CFs) composites using ferrocene as a catalyst. The Si/ CNTs/CFs anode exhibited good rate capability.…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts have been reported to overcome barriers against a long-life silicon-based anode for lithium-ion battery. Chemical passivation layers were coated on the surface of the silicon powder followed by an electrically conductive carbon layer [ 6 , 7 , 8 , 9 ]. The chemical passivation layers reduce undesirable reactions between silicon surface and the electrolyte, and thus enhance the coulombic efficiency and cycling life.…”
Section: Introductionmentioning
confidence: 99%